Imaging mass‐wasting sliding surfaces within complex glacial deposits along coastal cliffs using geophysics. Issue 9 (25th April 2022) - Blondel, Simon; Uhlemann, Sebastian; Inauen, Cornelia; Watlet, Arnaud; Maurer, Hansruedi; Jordan, Colm; Lee, Jonathan; Chambers, Jonathan
Abstract: This study presents a multidisciplinary survey combining geological fieldwork and geophysical data to better constrain the parameters influencing the morphology and behaviour of a retreating coastal cliff. Erosion rates are spatially highly variable and hard to predict because of the manifold parameters acting on them. Among these parameters, rock resistance exerts a paramount influence on cliff retreat. Characterizing the rock resistance distribution along a coastal region requires the mapping of several key subsurface properties including the bulk lithology, faulting, fracturing, or weathering. This is a difficult and expensive task because of the high spatial variability of these factors linked to the spatial complexity of the geology. Geophysical methods can be used to tackle this challenge by quickly providing the 3D visualization and distribution of these parameters within the subsurface. A fast‐eroding portion of the Norfolk coast (UK) at West Runton is investigated using a multidisciplinary approach, combining ground‐penetrating radar, electrical resistivity tomography (ERT), cone penetration tests, and outcrop studies. The results allowed us to build a 3D geological and geophysical model of a highly complex area of glacial geology. It forms part of a relict glaciotectonic thrust‐tip moraine and sand basin sequence. The surfaces interpreted on radar data are associated with strong resistivity contrasts on the ERT data. These contrasts have been attributed to petrophysical variations between the lithological units. The base of the sand basin is marked by a low‐permeability clay bed. Its low shear strength is likely to be more susceptible to failure, hereby accelerating the erosion rate of an already fast‐eroding sand basin. The resulting model can be used as input for locally constraining the ground parameters in coastal recession and erosion models. Abstract : A multidisciplinary approach combining electrical resistivity tomography, multi‐frequency 3D and 2D ground‐penetrating radar, cone penetration tests, and an outcrop study to characterize a coastal cliff prone to mass‐wasting and erosion. The soft material and the slipping surfaces are quickly delineated and the volume of sediments to be eroded is easily approximated. This approach can improve coastal recession models for coastal management, particularly in light of climate change and increasing climate extremes that may further accelerate coastal erosion.